The Influence of Information Prospectus, Share Offering Percentage, and Institutional Ownership Structure on Company Underpricing During an IPO - Sari, Putu Julia Indah; Hudaya, Robith (International Journal of Business and Applied Economics, 2025)
This study aims to determine the influence of the information prospectus, measured by the Debt-to-Equity Ratio, Return on Assets, and Current Ratio, as well as the percentage of stock offerings and institutional ownership structure, on underpricing. The population in this study consists of 168 companies conducting Initial Public Offerings during the 2020–2023 period. The analysis method employed is multiple linear regression analysis. The study results indicate that underpricing significantly affects the Debt-to-Equity Ratio, Return on Assets, and IPO Share Ownership Percentage. However, the Current Ratio and Institutional Ownership Structure do not have a significant effect. This research is expected to provide valuable insights into the mechanisms and factors influencing underpricing in the context of the Indonesian capital market. It can be a reference for investors and issuers when planning IPO strategies.